2003
DOI: 10.1021/ja030506s
|View full text |Cite
|
Sign up to set email alerts
|

Direct Structure Determination of a Multicomponent Molecular Crystal Prepared by a Solid-State Grinding Procedure

Abstract: A three-component molecular cocrystal material has been prepared by a solvent-free route involving mechanical grinding of the pure phases of the individual components. This material is not accessible from conventional solution-state crystallization procedures. Due to the fact that the grinding procedure intrinsically leads to a microcrystalline powder sample, the use of powder X-ray diffraction data is essential for structure determination. This work emphasizes the scope and utility of ab initio structure solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 17 publications
1
89
0
Order By: Relevance
“…Importantly, the resulting cocrystal could not be obtained from solution and so required structure determination from X-ray powder diffraction (see Section 9). [155] Sada et al [156] formed brightly colored charge-transfer complexes by mixing a palecolored electron donor, acting as an analyte, and a pale-coloured electron acceptor, acting as a probe, or vice-versa. A series of acceptor molecules was designed as probes to produce a 2D colorimetric indicator array which discriminated between isomers of organic molecules such as di-hydroxynaphthalene, using only the naked eye.…”
Section: Charge Transfer Cocrystalsmentioning
confidence: 99%
“…Importantly, the resulting cocrystal could not be obtained from solution and so required structure determination from X-ray powder diffraction (see Section 9). [155] Sada et al [156] formed brightly colored charge-transfer complexes by mixing a palecolored electron donor, acting as an analyte, and a pale-coloured electron acceptor, acting as a probe, or vice-versa. A series of acceptor molecules was designed as probes to produce a 2D colorimetric indicator array which discriminated between isomers of organic molecules such as di-hydroxynaphthalene, using only the naked eye.…”
Section: Charge Transfer Cocrystalsmentioning
confidence: 99%
“…Indeed, a notable example of a solid-state mechanochemical synthesis of a molecular materials coupled with structure determination from PXRD data was reported in 2003 by Cheung et al 42 who described the formation and characterization of a three-component cocrystal of benzoquinone, anthracene, and racemic bis-β-naphthol obtained by manual grinding of the three components. The report by Karki et al 43 demonstrated the mechanochemical ball-milling synthesis of two model organic pharmaceutical cocrystals, followed by structural characterization using PXRD data and thermogravimetric analysis.…”
Section: 41mentioning
confidence: 99%
“…Studying mechanisms of mechanochemical reactions could be very difficult [10] and many methods are used (in situ diffraction of high-energy synchrotron X-rays [11], ESCA [12]). The use of powder X-ray diffraction data is essential for structure determination [13]. The reaction profiles are directly monitored, as well as the formation of intermediates, interconversions of framework topologies [10], mechanochemical screening for molecular recognition is usually done [11].…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…Wixtrom et al [9] described an undergraduate organic chemistry experiment, the reaction of tetrathafulvalene and chloranil involving liquid-assisted grinding. Cheung et al [13] have prepared a three component molecular cocrystal material via a solvent-free route involving the mechanical grinding of pure phases of the individual components. Garay et al [6] introduced the synthesis of mononuclear complex, coordination clusters, spacious coordination cages, and 1-, 2-and 3-dimesional coordination polymers.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%